A Novel Homozygous Intronic Variant in TNNT2 Associates With Feline Cardiomyopathy - McNamara, James W.; Schuckman, Maggie; Becker, Richard C.; Sadayappan, Sakthivel (Frontiers in Physiology, 2020)
Background Hypertrophic cardiomyopathy (HCM) is a genetic disease of the heart and the most common cause of sudden cardiac death in the young. HCM is considered a disease of the sarcomere owing to the large number of mutations in genes encoding sarcomeric proteins. The riddle lies in discovering how these mutations lead to disease. As a result, treatments to prevent and/or treat HCM are limited to invasive surgical myectomies or ablations. The A31P variant of cardiac myosin binding protein-C, encoded by MYBPC3, was found to be more prevalent in a cohort of Maine Coon cats with HCM. However, other mutations in MYBPC3 and MYH7 have also been associated with HCM in cats of other breeds. In this study, we expand the spectrum of genes associated with HCM in cats. Results Next Generation Whole Genome sequencing was performed using DNA isolated from peripheral blood of a Maine Coon with cardiomyopathy that tested negative for the MYBPC3 A31P variant. Through risk stratification of variants, we identified a novel, homozygous intronic variant in cardiac troponin T (TNNT2). In silico analysis of the variant suggested that it may affect normal splicing of exon 3 of TNNT2. Both parents tested heterozygous for the mutation, but were unaffected by the disease. Echocardiography analyses revealed that the proband had shown early onset congestive heart failure, which is managed with a treatment regime including ACE and aldosterone inhibitors. Conclusion In summary, we are the first to demonstrate the association between TNNT2 mutations and HCM in felines, suggesting that this gene should be included in the testing panel of genes when performing genetic testing for HCM in cats.